2005
DOI: 10.1590/s0100-879x2005000600013
|View full text |Cite
|
Sign up to set email alerts
|

Leptospira interrogans activation of peripheral blood monocyte glycolipoprotein demonstrated in whole blood by the release of IL-6

Abstract: Glycolipoprotein (GLP) from pathogenic serovars of Leptospira has been implicated in the pathogenesis of leptospirosis by its presence in tissues of experimental animals with leptospirosis, the inhibition of the Na,K-ATPase pump activity, and induced production of cytokines. The aims of the present study were to investigate the induction of IL-6 by GLP in peripheral blood mononuclear cells (PBMC) and to demonstrate monocyte stimulation at the cellular level in whole blood from healthy volunteers. PBMC were sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 14 publications
0
12
0
1
Order By: Relevance
“…It was later demonstrated that the GLP induced cytokine production in peripheral blood monocytes from healthy volunteers. 4,5 The presence of inflammatory cytokines has also been confirmed in sera of patients with leptospirosis. 6 Marinho and others 7,8 showed that high levels of tumor necrosis factor (TNF)-a and interleukin (IL)-6 in the supernatant of peritoneal macrophage cellular culture of genetically selected mice inoculated with a sample of Leptospira interrogans serovars Canicola was determined by immunoenzymatic assays.…”
Section: Introductionmentioning
confidence: 92%
“…It was later demonstrated that the GLP induced cytokine production in peripheral blood monocytes from healthy volunteers. 4,5 The presence of inflammatory cytokines has also been confirmed in sera of patients with leptospirosis. 6 Marinho and others 7,8 showed that high levels of tumor necrosis factor (TNF)-a and interleukin (IL)-6 in the supernatant of peritoneal macrophage cellular culture of genetically selected mice inoculated with a sample of Leptospira interrogans serovars Canicola was determined by immunoenzymatic assays.…”
Section: Introductionmentioning
confidence: 92%
“…Thus, the elevated MBL levels found in the patients from 2001 could be related to the inflammatory response and the presence of Leptospira virulence factors such as glycoprotein of pathogenic Leptospira (17). The lower levels of MBL found in the 2002 group suggest that the inflammatory response to infection was milder due to an effective immune response or the lack of Leptospira virulence factors in most cases.…”
Section: Discussionmentioning
confidence: 91%
“…Dorigatti et al (17), using glycoprotein of pathogenic L. interrogans serovar Copenhagen from a patient with Weil's syndrome, demonstrated the induction of IL-6 production and activation of monocytes by this component. Thus, the elevated MBL levels found in the patients from 2001 could be related to the inflammatory response and the presence of Leptospira virulence factors such as glycoprotein of pathogenic Leptospira (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by Dorigatti et al 4 has shown that OMP of pathogenic Leptospira when inoculated to tubular cells in culture activated nuclear NF Kappa B binding and stimulated downstream inducible nitric oxide (INOS), monocyte chemoattractant protein-1 (MOP-1) and tumor necrosis factor. Another study reported by Magrinho et al 5 detected TNFα and IL-6 in rat renal experimentally infected with L.canicola.…”
Section: Discussionmentioning
confidence: 99%